Praktik Klasifikasi Arsip Siaran: Studi Kasus pada Stasiun Radio LPP RRI Malang, Kalimaya Bhaskara FM dan City Guide FM - Candraningtyas, Zsa Zsa; Safii, Moh.; Ansor, Sokhibul (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Classification of audio archives is one of the challenges for radio stations in managing their audio to maintain the sustainability of the information they have. This study aims to adjust the implementation of broadcast archive classification at the LPP RRI Malang, Kalimaya Bhaskara FM, and City Guide FM stations with Schellenberg's opinion (1956). This study uses a qualitative case study approach method to explore the stages of implementation of audio archive classification carried out by each radio station. The selection of informants was carried out using purposive sampling techniques and using spiral data analysis by Creswell to compile the data to be presented. The results of the study indicate that the implementation of audio archive classification at radio stations involves software, internal organizational policies, and the use of metadata in the archive classification process. The challenges found include the use of metadata, consistency of classification schemes, and limited understanding of human resources. This study needs to provide archival training to any agency not specifically for archives and the preparation of rules or standards for managing audio archives, especially in their classification, to improve operational effectiveness in the long term and optimize information preservation.